CALCULATION MODEL OF GRAIN GRAVITATION MOVEMENT IN SLOPING PASSAGE WITH DISCRETE VARIABLE INCLINATION ANGLE - Arendarenko, V. M.; Antonets, A. V.; Savchenko, N. K.; Samoilenko, T. V.; Ivanov, O. M. (Scientific Progress & Innovations, 2020)
The wholeness of grain loaded into the silo depends on the method of its delivery to the concrete bottom of this structure. Special devices are used for this purpose. They can operate on the principle of emptying, rain, and with the use of braking devices. Peripheral open screw passages slow down the movement of grain, but it is unknown how the angle of brake section depends on the angle of acceleration section of the device. The purpose of this work is to investigate theoretically the movement of grain flow in an installation with discretely variable inclination angles of acceleration and brake trays. The main task was to substantiate the dependence of inclination angle of the brake tray on inclination angle of the acceleration tray. To study the movement of grain on sloping areas and reduce its injury, a gravitation installation consisting of acceleration and brake trays (open trays) has been proposed in this article. Grain flow accelerates its speed to maxVon acceleration tray passing the way 1l along the acceleration tray, which is located at an angle α to the horizon. This occurs as a result of the transition of part of grain potential energy 11sinпEmglα= to kinetic energy due to the inclination of the acceleration tray at an angle of α.In the second section, the grain slows down. That is, it begins to move without acceleration. The speed of grain pouring in the storage hopper becomes close to the initial speed of grain material on the acceleration tray. For the normal grain flow movement along the entire length of the acceleration and brake trays, it is necessary that the angles α and β are bigger than the angle of the natural slope ζ. Grain flow movement along the brake tray having the length 2l placed at an angle β to the horizon, is due to the previously acquired maximum kinetic energy and grain potential energy22sinпEmglβ=. Thus, using the installation with discretely variable angles of acceleration and brake trays, it is possible to conduct experiments to study the speed of different types of grain material movement in the final stage of loading cylindrical tanks.